Factor Analysis of Student Social Skills of Co-curricular Participants at Polytechnic - Indroasyoko, N.; Muhammad, A.; Sujana, D. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2019)
The objective of this research is to know how big the impact of co-curricular program to social skill. Samples are 59 the students of Politeknik Manufaktur Bandung who follow the activities of co-curricular field of Arts, Special Skills and Sports. Attributes of Social Skills include: Co-operation, Assertiveness, Empathy, and Self-Control. The questionnaire technique using the scale of assessment of Linkert model. The data were analyzed by using factor analysis to find out which factors were dominant and how the ranking variables. The results showed that students of co-curricular participants could form social skills by 66%, while the social skill formation by the co-curricular in the respective fields: art-62.44%, special skills-59.22%, and sports-81, 78%, the rest in the stimulus by other factors that have not been revealed. The co-curricular field of sports contributes the most dominant in the formation of students' social skills compared to other fields. There is a variation in the sequence of dominant factors of social skills variables for each field of co-curricular activity. The dominant of the social skills of each co-curricular programs differs. In terms of art skill, the dominant factor is self-control. In relation to specific technical skill, empathy dominates the factor. Meanwhile in sport skill, the factor is dominated by assertiveness.